Effects of mental fatigue on biomechanical characteristics of lower extremities in patients with functional ankle instability during unanticipated side-step cutting - Kong, Lingyu; Wu, Peng; Zhang, Xinwen; Meng, Lingyue; Kong, Lintao; Zhang, Qiuxia; Shen, Jianzhong (Frontiers in Physiology, 2023)
Background: Functional ankle instability (FAI) is the primary classification of ankle injuries. Competitive activities have complicated movements that can result in ankle re-injury among patients with FAI. Unanticipated movement state (MS) and mental fatigue (MF) could also happen in these activities, which may further increase their joint injury risk. Objective: This study aimed to clarify the biomechanical characteristics difference of the lower extremity (LE) between the injured side and the uninjured side among patients with FAI when they perform unanticipated side-step cutting after MF. Methods: Fifteen males with unilateral FAI participated in this study (age: 20.7 ± 1.3 years, height: 173.6 ± 4.4 cm, weight: 70.1 ± 5.0 kg). They used the injured side and the uninjured side of LE to complete anticipated and unanticipated side-step cutting before and after MF. The kinematic and kinetics data were evaluated using three-way ANOVA with repeated measures. Results: During patients with FAI performed anticipated side-step cutting, the ankle stiffness of both sides showed no significant change after MF; During they performed unanticipated side-step cutting, their injured side presented significantly lower ankle stiffness after MF, while the uninjured side did not have such change. In addition, after MF, the injured side exhibited increased ankle inversion, knee valgus and LR, but the uninjured side did without these changes. Conclusions: Influenced by MF, when patients with FAI use their injured side of LE to perform side-step cutting, this side has a higher risk of musculoskeletal injuries such as lateral ankle sprains and anterior cruciate ligament injury. The ankle stiffness of the injured side will be further reduced when patients with FAI perform unanticipated side-step cutting, which increases ankle instability and the risk of re-injury.